Стратегічні напрями зниження енергоємності промислового виробництва України на період до 2015 року - Symborskiy A.I. (General Energy Institute of the National Academy of Sciences of Ukraine, 2004)
The main directions of power capacity decline in Ukrainian industry production in the long-term period are considered.